2013
DOI: 10.1111/gwat.12032
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Discrete Fracture and Continuum Models to Predict Contaminant Transport in Fractured Porous Media

Abstract: We used the FRAC3Dvs numerical model (Therrien and Sudicky 1996) to compare the dual-porosity (DP), equivalent porous medium (EPM), and discrete fracture matrix diffusion (DFMD) conceptual models to predict field-scale contaminant transport in a fractured clayey till aquitard. The simulations show that the DP, EPM, and DFMD models could be equally well calibrated to reproduce contaminant breakthrough in the till aquitard for a base case. In contrast, when groundwater velocity and degradation rates are modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 33 publications
0
30
0
1
Order By: Relevance
“…Longitudinal dispersivity (α L ) for the matrix domain was taken from Helmke et al (, ). The α L value for the fracture domain was fit using published values for fractured till (Table ; Blessent et al ). The resulting cumulative breakthrough curve from the dual‐continuum model demonstrated good agreement with the results of the column experiment, showing a modified index of agreement value ( d 1 ) of 0.97 (Willmott et al ; Helmke et al ; Figure ).…”
Section: Performance Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinal dispersivity (α L ) for the matrix domain was taken from Helmke et al (, ). The α L value for the fracture domain was fit using published values for fractured till (Table ; Blessent et al ). The resulting cumulative breakthrough curve from the dual‐continuum model demonstrated good agreement with the results of the column experiment, showing a modified index of agreement value ( d 1 ) of 0.97 (Willmott et al ; Helmke et al ; Figure ).…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Single‐ and dual‐continuum models have been used to upscale groundwater flow in fractures (Sudicky ; Gerke and van Genuchten ; Helmke et al ; Blessent et al ). Representing fracture‐induced anisotropy requires a 3D, six‐component K tensor (symmetry assumed) for the fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five 3D soil and groundwater flow and substance transport models were found that simulate preferential flow and transport, including HILLFLOW [36], TOUGH2 [37], HYDRUS-3D [38], MIKE-SHE [12,13], and a model by Laine-Kaulio et al [39]. In addition, Blessent et al [40] used the FRAC3Dvs numerical model to compare the dual porosity, equivalent porous medium, and the discrete fracture matrix diffusion conceptual model, and the study has an important role in decision-making for groundwater-related issues, while the research focus is the 2 Geofluids groundwater and the three models do not consider the surface runoff movement. Although soil swelling and shrinkage models have been included in several earlier models, most notably in FLOCR [41], MACRO [42], and SWAP [43], they are all limited to 1D or quasi 2D simulations.…”
Section: Introductionmentioning
confidence: 99%
“…As diferentes abordagens podem ser agrupadas em três classes: meio poroso equivalente, o modelo de dupla porosidade, e o modelo de rede de fraturas discretas (Cook, 2003) (Blessent, et al, 2014). A continuação, são apresentadas as características principais de cada modelo conceitual respeito ao fluxo e ao transporte de contaminantes em meios porosos e meios porosos fraturados.…”
Section: Modelos Conceituais Do Fluxo E Transporte Em Meio Poroso Fraunclassified